PERANCANGAN MESIN PENGADUK PAKAN TERNAK BERKAPASITAS 75 kg MENGGUNAKAN SISTEM ARDUINO - Djoko W Karmiadji; Zulfikri Sy Tampa (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
The need for animal feed in Indonesia is very high because of the increasing demand for processed meat. And one of the reasons is also due to the government's program to meet Indonesia's food security to reduce dependence on meat imports. To support this, animal feed is one of the key factors to improve the quality of livestock. The feed mixer machine is a solution to make it easier for breeders to mix the feed mixture. With this machine will cut costs and production time for farmers to produce the feed. The result obtained is design data in the form of machine images using Solidwork software. The frame of this machine uses hollow 1023 Carbon Steel Sheet 40 × 40 mm with a thickness of 2 mm and the body of this machine uses ASTM A36 Steel material thickness of 2 mm. The overall dimensions of this engine are 1400 mm long, 665 mm wide and 1133 mm.